An Analysis of Cohesive Devices in EFL Students' Essay Writing - Siregar, Jumaini; Nurlela, Nurlela; Zein, T. Thyrhaya (Indonesian Journal of EFL and Linguistics, 2023)
Students need to be able to make effective use of cohesive devices in order to produce high-quality essays. This research aimed to investigate the use of cohesive devices in EFL students’ essay writing in the 2nd Semester of the English Language Department at a State University in North Sumatera. The data sources of this research were essays and transcripts of interviews. The method used in this research was qualitative content analysis and case study. The model used in data analysis were frequency count and content analysis by applying interactive models such as data collection, data condensation, data display, and conclusion. The research finding showed that Reference (59%) was the predominant grammatical cohesive device used by EFL students in essay writing compared to other types. Meanwhile, Ellipsis (0.3%) was the lowest. Moreover, compared to lexical cohesive devices, EFL students used Repetition at the highest rate (89%) in their essay writing whereas the percentage of Hyponyms used was the lowest (0.3%), however, Meronyms did not appear in this research. Furthermore, the students had adequate knowledge to apply grammatical cohesive devices appropriately (990 data), as opposed to the incohesive use acquired (105 data). Whereas in terms of lexical cohesive devices, all the phrases are cohesive. In this regard, the reasons for incohesive writing by students are interference from their native language and overgeneralization whereas the interference of the learning context is not found in this study. In conclusion, the understanding of cohesive devices can improve and embellish the knowledge in building a good and true sentence. This is also useful in avoid students from writing inappropriate sentences. Therefore, English writing lecturers are expected to help students facing obstacles such as the use of cohesive devices by applying explicit teaching and increasing their performance in terms of cohesive devices in essay writing.